Size distribution of Haliotis asinina and abundance of periphyton in tapulaga waters - Ermayanti Ishak; Muhammad Taswin Munier; Muhammad Trial (Depik, 2025)
The Tapulaga waters, located in Soropia, Southeast Sulawesi, are among the coastal waters with significant potential for the seven-eyed abalone (Haliotis asinina). This species is a herbivorous gastropod that primarily consumes natural food sources such as periphyton and macroalgae. This study aims to determine the size distribution of H. asinina and analyze the presence of periphyton on seagrass leaves and macroalgal thalli. Sampling was conducted over six months in the Tapulaga waters of Soropia, Konawe Regency, Southeast Sulawesi, using a simple random sampling technique. The collected data were analyzed using descriptive statistical methods. The results indicate that the highest percentage of size distribution was observed in the range of 37.544.5 mm, comprising 34% of the total population. The population was categorized into two size groups: juveniles ( 49 mm) and adults ( 50 mm). Juveniles accounted for 75% of the total H. asinina population, while adults comprised 25%. A total of 11 periphyton species from three taxonomic classes Bacillariophyceae, Cyanophyceae, and Trebouxiophyceaewere identified on the seagrass species Enhalus acoroides and the macroalgae Gracilaria salicornia, Padina sp., Halimeda sp., Galaxaura sp., and Gelidium sp. The identified periphyton species included Aulacoseira sp., Nitzschia sp., Synedra sp., Diatoma sp., Fragilaria sp., Navicula sp., Pinnularia sp., Melosira sp., Lyngbya sp., Planctonema sp., and Cocconeis sp. Six of these periphyton species were present on both seagrass and macroalgal thalli. Synedra sp. was the most dominant species, exhibiting the highest abundance at 88,876 individuals/cm. The presence of periphyton as a natural food source attached to seagrass leaves and macroalgal thalli plays a crucial role in supporting the juvenile H. asinina population.Keywords:H. asininaMacroalgaePeriphytonTapulaga